Late-time H/He-poor Circumstellar Interaction in the Type Ic Supernova SN 2021ocs: An Exposed Oxygen-Magnesium Layer and Extreme Stripping of the Progenitor - Kuncarayakti H.; Maeda K.; Dessart L.; Nagao T; Fulton M; Gutiérrez C; Huber M.E.; Young D.R.; Kotak R; Mattila S.; Anderson J.P.; Ferrari L.; et al. (IOP Publishing, 2025)
Supernova (SN) 2021ocs was discovered in the galaxy NGC 7828 (z = 0.01911) within the interacting system Arp 144 and subsequently classified as a normal Type Ic SN around peak brightness. Very Large Telescope/FORS2 observations in the nebular phase at 148 days reveal that the spectrum is dominated by oxygen and magnesium emission lines of different transitions and ionization states: O i, [O i], [O ii], [O iii], Mg i, and Mg ii. Such a spectrum has no counterpart in the literature, though it bears a few features similar to those of some interacting Type Ibn and Icn SNe. Additionally, SN 2021ocs showed a blue color, (g − r) ≲ −0.5 mag, after the peak and up to late phases, atypical for a Type Ic SN. Together with the nebular spectrum, this suggests that SN 2021ocs underwent late-time interaction with an H/He-poor circumstellar medium (CSM) resulting from the pre-SN progenitor mass loss during its final ∼1000 days. The strong O and Mg lines and the absence of strong C and He lines suggest that the progenitor star's O–Mg layer is exposed, which places SN 2021ocs as the most extreme case of a massive progenitor star's envelope stripping in interacting SNe, followed by Type Icn (stripped C–O layer) and Ibn (stripped He-rich layer) SNe. This is the first time such a case is reported in the literature. The SN 2021ocs emphasizes the importance of late-time spectroscopy of SNe, even for those classified as normal events, to reveal the inner ejecta and progenitor star's CSM and mass loss.